Majalah Gontor. - Gontor Media Jaya, PT. (Jakarta : Gontor Media Jaya)
On Islam and related religious issues in Indonesia.
Description based on: Edisi 3, Th. I (Juli 2003).
Keywords: Islam -- Indonesia -- Periodicals